Cargo Sorting in the Endocytic Pathway: A Key Regulator of Cell Polarity and Tissue Dynamics - Eaton, Suzanne (Cold Spring Harbor Laboratory Press, 2014)
The establishment and maintenance of polarized plasma membrane domains is essential for cellular function and proper development of organisms. Epithelial cells polarize along two fundamental axes, the apicobasal and the planar, both depending on finely regulated protein trafficking mechanisms. Newly synthesized proteins destined for either surface domain are processed along the biosynthetic pathway and segregated into distinct subsets of transport carriers emanating from the trans-Golgi network or endosomes. This exocytic trafficking has been identified as essential for proper epithelial polarization. Accumulating evidence now reveals that endocytosis and endocytic recycling play an equally important role in epithelial polarization and the appropriate localization of key polarity proteins. Here, we review recent work in metazoan systems illuminating the connections between endocytosis, postendocytic trafficking, and cell polarity, both apicobasal and planar, in the formation of differentiated epithelial cells, and how these processes regulate tissue dynamics.